2020
DOI: 10.1063/1.5135774
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of particle cloud dispersion in compressible gas flows with shock waves

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Such phenomenon is also observed in other studies, e.g., in Refs. [11,31]. However, the RPW is not significant for small WDs (e.g., d d,0 = 5-20 μm in our previous study [17]) as it is too weak to be observed.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Such phenomenon is also observed in other studies, e.g., in Refs. [11,31]. However, the RPW is not significant for small WDs (e.g., d d,0 = 5-20 μm in our previous study [17]) as it is too weak to be observed.…”
Section: Resultscontrasting
confidence: 52%
“…It is not intended to capture the detailed morphology of either the shock or WDs as such topics have been stressed in the previous studies with two-or three-dimensional configurations [1,10,12,[14][15][16]27,28]. The 1D simplification also has been widely used for particle [29][30][31] or droplet [11,13,32,33] laden flows with shocks. Figure 1(a) shows a schematic of the 1D domain (x = 0-1.6 m) and the initial distribution of WDs.…”
Section: Physical Problemmentioning
confidence: 99%
“…Therefore, it is nontrivial to compute particle forces in such problems, and while many studies have performed simulations of this kind, e.g. [1,2,3,4], it is unclear whether the physical processes at particle scale are well represented, and therefore whether or not the results are reliable. This motivates a detailed assessment of the performance of classical drag laws in problems featuring dense particle suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, there have been many theoretical and experimental studies investigating the physics of the interaction of droplets or solid particles/obstacles with shock waves (Carrier 1958;Rudinger 1964;Olim et al 1990;Geng et al 1994;Chaudhuri et al 2012Chaudhuri et al , 2013Balakrishnan & Bellan 2017;Mouronval et al 2019;Gai et al 2020). Commonly, the particles are assumed to be at rest before they meet the shock at a given velocity.…”
Section: Introductionmentioning
confidence: 99%
“…2019; Gai et al. 2020). Commonly, the particles are assumed to be at rest before they meet the shock at a given velocity.…”
Section: Introductionmentioning
confidence: 99%